2015
DOI: 10.1515/pac-2015-0302
|View full text |Cite
|
Sign up to set email alerts
|

In vitro photoprotection and antioxidant capacity of Sphagnum meridense extracts, a novel source of natural sunscreen from the mountains of Colombia

Abstract: Excessive ultraviolet radiation can cause skin cancer and related health problems in humans. Traditionally, organic and inorganic sunscreens have been used to minimize these effects. Besides, some phenolic compounds present in plants play an important role as photoprotectors. Sphagnum meridense (L), found in Colombia, is continuously exposed to sunlight on high mountain ecosystems. In this work, we evaluated the potential of S. meridense extracts to be applied as UVA-UVB filter in cosmetic formulations and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…The total phenolic content (TPC) of the samples was measured using a modified colorimetric Folin‐Ciocalteu method . Briefly, 10 μL of extract solution and 615 μL of deionized water were added to a test tube.…”
Section: Methodsmentioning
confidence: 99%
“…The total phenolic content (TPC) of the samples was measured using a modified colorimetric Folin‐Ciocalteu method . Briefly, 10 μL of extract solution and 615 μL of deionized water were added to a test tube.…”
Section: Methodsmentioning
confidence: 99%
“…However, TPC values decrease when activated carbon is added due to the low selectivity of activated carbon that not only adsorbs chlorophylls but may also be absorbing other types of compounds, such as polyphenols, as previously reported in B. antioquensis extracts, a plant of the same family Asteraceae [45]. In previous studies carried out by us and various publications have shown that the addition of acids, mainly HCl, increases the yield of polyphenol extraction [33,45,49,50], as observed in this study (Table 2 tests 1, 2, 3, and 4). The reason why we discarded the extracts where HCl was used was due to the poor sensory characteristics of these formulations, since the incorporation of these extracts was not adequate in the hydrogel, presenting brown colorations and large dispersed particles.…”
Section: Resultsmentioning
confidence: 67%
“…The antioxidant capacity was measured by the inhibition of lipid peroxidation in MeLo, through the production of conjugated diene hydroperoxide (CDH) and thiobarbituric acid reactive substances (TBARS), using the method described by Mejía-Giraldo et al [33]. Solutions of MeLo 10 mM (negative control), MeLo plus BHT 0.02% w/v (positive control), and MeLo plus 0.02% (w/v) of each extract were exposed to accelerated oxidation by heating at 40 ± 5 °C for 5 days in test tubes.…”
Section: Antioxidant Activity-lipid (Melo) Modelmentioning
confidence: 99%
“…The antiradical ability of all extracts was determined using the DPPH• test as free radical (24,25). For each extract, different concentrations were evaluated and the radical scavenging activity was calculated, expressed as the number of mg of antioxidant substance (dry extract) necessary to reduce the initial concentration of the DPPH• radical by 50% and was expressed as the concentration effective (EC 50 ).…”
Section: Methodsmentioning
confidence: 99%
“…The antioxidant capacity was measured by the inhibition of lipid peroxidation in methyl linoleate (MeLo), through the production of conjugated dienes (CD) and thiobarbituric acid reactive substances (TBARS), using the method described by Mejía‐Giraldo et al . (26). Solutions of MeLo (10 mM), MeLo plus BHT 0.02% (w/v) and MeLo plus 0.02% (w/v) of each of the extracts were exposed to accelerated oxidation by heating at 40 ± 5°C for 5 days in test tubes.…”
Section: Methodsmentioning
confidence: 99%